Conformations and Biological Activities of Amyloid Beta Peptide 25-35 - Millucci, L.; Ghezzi, L.; Bernardini, G.; Santucci, A. (Current Protein and Peptide Science, 2010)
Amyloid-β (Aβ) peptide is commonly found in human Alzheimer's disease (AD) brain and is the main component of Alzheimer amyloid plaques. The predominant forms of Aβ in the human brain are Aβ(1-40) and Aβ(1-42), but Aβ(25-35) fragment, physiologically present in elderly people, is the more toxic region and has been recently found to play a relevant role in AD, due to its peculiar aggregation properties. In this work, we review the current understanding on the conformations and biological activity of Aβ(25-35) exploring aggregation, cytotoxic and neurodegenerative properties of this fundamental Aβ fragment, in order to provide an effective starting point to better approach a pathology spread and problematic as AD.
Keywords: Alzheimer' s disease